Cracking and Improvement of an Image Encryption Algorithm Based on Bit-Level Permutation and Chaotic System - Wang Xingyuan (IEEE Access, 2019)
In recent years, with the rapid development of the network communication, information security issues have become increasingly prominent. As an important carrier of information, image plays an important role in the transmission process. Therefore, lots of image encryption algorithms have been proposed. However, these algorithms are not designed in accordance with the unified security standards and requirements, so there may be a lot of security risks, and what is the worst thing is that some encryption algorithms may be cracked in an acceptable time complexity by some cryptographic analysis. This paper focuses on one of the most influential algorithm proposed by Zhang, which improved Zhu's algorithm. The non-fixed parameter and diffusion-permutation strategy are adopted by Zhang, but there are still problems that cannot resist chosen-plaintext attack and the key space is not enough to resist brute-force attack. We use chosen-plaintext attack to crack Zhang algorithm, and then propose a further improved scheme.